1992
DOI: 10.1111/j.1151-2916.1992.tb04392.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Effects in the Sol–Gel Preparation of PZT Dried Gels, Powders, and Ferroelectric Thin Layers

Abstract: Infrared spectroscopy was used to monitor and characterize solutions used in the preparation of PZT 53/47 powders, dried gels, and thin layers deposited on platinized silicon substrates. It was found that careful control of the chemistry of the precursor solutions, in particular the control of the formation of esters and their elimination, resulted in reproducible solutions which could be used to prepare thin layers with superior properties. In addition, it was found that phase development and microstructure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(55 citation statements)
references
References 7 publications
2
53
0
Order By: Relevance
“…Similarly, previous study of Lakeman and Payne showed that in PZT gels all reactions were completed at lower temperature in low water gels (Rw: 2.0 and 3.0) whereas high water gels (Rw: 10) displayed more diffuse behavior with several peaks and required higher temperature to complete the reaction [22,23]. It is possible to correlate this behavior with the formation and the development of the perovskite phase.…”
Section: Effect Of Hydrolysis Ratiosupporting
confidence: 64%
“…Similarly, previous study of Lakeman and Payne showed that in PZT gels all reactions were completed at lower temperature in low water gels (Rw: 2.0 and 3.0) whereas high water gels (Rw: 10) displayed more diffuse behavior with several peaks and required higher temperature to complete the reaction [22,23]. It is possible to correlate this behavior with the formation and the development of the perovskite phase.…”
Section: Effect Of Hydrolysis Ratiosupporting
confidence: 64%
“…The solution chemistry that was employed follows the synthesis route developed by Budd et al 17 and later refined by Lakeman and Payne, 18 for the fabrication of Pb-based perovskite thin films on a substrate. The substrate consisted of a single-side polished Si ͑100͒ wafer with a 5000 Å thermally grown oxide and a nominal thickness of 375 m ͑Sili-con Quest International, Inc., Santa Clara, CA͒.…”
Section: A Film Depositionmentioning
confidence: 99%
“…This peak was attributed to the decomposition of most of the bound organic species. The weight loss proceeded even after 300 o C, yielding a constant value near 600 o C. It has been demonstrated by Payne et al 18 that the exothermic feature at higher temperature region varies with process conditions. They discussed the position of the higher exothermic peak observed at ~500-600 o C which varied with water content.…”
Section: Resultsmentioning
confidence: 81%
“…The relative amounts of perovskite and pyrochlore phases were determined by measuring the relative intensity of XRD peaks by using the following equation 18 : % perovskite = The amount of perovskite phase formed was promoted with increasing seed content incorporated in the gels, and consequently the formation temperature of pure perovskite phase was lowered as the seed content was increased. As the perovskite nucleation site density increased with the increase of seed concentration, the amount of perovskite phase also increased.…”
Section: Resultsmentioning
confidence: 99%